Relationship Between Storage and Recording with Quality of DPT Vaccine Cold Chain in Puskesmas - Hikmarida, Faradiba (Jurnal Berkala Epidemiologi, 2014)
ABSTRACTIncreasing number of diphteria cases in Sidoarjo Regency, with occurrence of cases in those who had received DPT immunization shows the existence of problem concerning to immunization. The efficacy itself, depends on the quality of vaccines given. Insufficiency in cold chain may lower the quality of DPT vaccines. The purpose of this study was to analyze relationship between DPT vaccine storage and recording for DPT vaccines cold chain with quality of DPT vaccine cold chain in puskesmas Sidoarjo Regency. This research is a descriptive research with cross sectional design. Sample used were total population, which includes all 26 puskesmas within Sidoarjo. The variables were DPT vaccine storage, recording for DPT vaccines cold chain and quality of DPT vaccine cold chain. The result of this study showed that DPT vaccine storage was good (58%), recording for DPT vaccines cold chain were insufficient (77%), and quality of DPT vaccine cold chain in puskesmas was also good (62%). Spearman correlation test showed relationship between DPT vaccine storage and quality of DPT vaccine cold chain in Puskesmas was strong and positive (r = 0,561). Relationship between recording for DPT vaccines cold chain and quality of DPT vaccine cold chain in puskesmas was moderate and positive (r = 0,421). the better the storage for DPT vaccines and recording for DPT vaccines cold chain in puskesmas, the better its cold chain quality in puskesmas. Improvement in officersâ obedience in storing DPT vaccine and its recording concerning to the cold chain which appropriate according to procedures, were really needed.Keywords: storage, recording, quality, cold chain, DPT vaccine